Trifluoroethanol-promoted ring-opening cyclization of 4-(2-oxiranylmethoxy)indoles: access to 4, 5-fused indoles. Issue 31 (21st July 2021) - Das, Jonali; Das, Sajal Kumar
Abstract : Pyrano[2, 3- e ]indol-3-ols and oxepino[4, 3, 2- cd ]indol-3-ols, have been synthesized via trifluoroethanol-mediated endo -selective ring-opening cyclization of 4-(2-oxiranylmethoxy)indoles. Abstract : Herein, we report that the trifluoroethanol-mediated ring-opening cyclization of readily accessible 4-(2-oxiranylmethoxy)indoles takes place in a diastereoselective and 6- endo fashion to generate pyrano[2, 3- e ]indol-3-ols in high yields. This regioselective cyclization at the indole C-5 position requires the presence of a π-activating aryl substituent on the reacting epoxide carbon atom, but remains uninfluenced by the electronic nature of the indole- N -substituent. Interestingly, blocking the C-5 position of the indole unit directs the reaction to generate oxepino[4, 3, 2- cd ]indol-3-ols via 7- endo epoxide–arene cyclization.